2021
DOI: 10.7759/cureus.16372
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Second Primary Malignancy and Mortality at ten Years After Stem Cell Transplant for Multiple Myeloma: An Analysis of 14,532 Patients

Abstract: BackgroundThe landscape for patients with multiple myeloma has improved dramatically over the last 15 years. Immunomodulatory imide drugs (IMiDs) have shown great efficacy in both the setting of initial therapy and as maintenance after autologous stem cell transplant (ASCT). Concern has arisen, however, regarding the risk of second primary malignancies (SPMs) that appear to be associated with the use of IMiD agents. SPMs are a known sequela of multiple myeloma treatment, particularly as a consequence of mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Eleven patients tested negative for the BCR/ABL fusion gene (one case was not tested). Karyotyping was performed in six patients; only one patient had complex cytogenetics of 42, X,-Y,Del(1)(p12p31), +der (1), -10,-13,-16,-21 [ 1 ]/46,XY [ 2 ], and the other five patients had a normal karyotype. Six patients received induction therapy (vincristine + daunorubicin/idarubicin + prednisone ± pegaspargase); two of these patients subsequently underwent allogeneic hematopoietic stem cell transplantation; they were still disease-free survivors (DFS) until now.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven patients tested negative for the BCR/ABL fusion gene (one case was not tested). Karyotyping was performed in six patients; only one patient had complex cytogenetics of 42, X,-Y,Del(1)(p12p31), +der (1), -10,-13,-16,-21 [ 1 ]/46,XY [ 2 ], and the other five patients had a normal karyotype. Six patients received induction therapy (vincristine + daunorubicin/idarubicin + prednisone ± pegaspargase); two of these patients subsequently underwent allogeneic hematopoietic stem cell transplantation; they were still disease-free survivors (DFS) until now.…”
Section: Resultsmentioning
confidence: 99%
“…The application of autologous hematopoietic stem cell transplantation (ASCT) and novel agents has significantly prolonged the survival of patients with multiple myeloma (MM), and secondary primary malignancies (SPM) have attracted increasing attention [ 1 , 2 , 3 ]. Large population-based studies showed that MM patients had a 26% increased risk of developing any SPM when compared to the general population [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Так, в одном из популяционных исследова ний, охватывающих данные по 14,5 тыс. пациентов с ММ из 49 крупных медицинских центров США, при сроке наблюдения 5 лет вторые первичные злокачест венные опухоли были диагностированы у 22,4 % па циентов, получивших ВДХТ и аутоТГСК, и у 16,6 % па циентов, не получивших трансплантации (p <0,0001) [14]. У пациентов, проживших 10 лет и более, данная проблема возникла уже в 42,3 и 40,8 % случаев соот ветственно (p = 0,0279).…”
Section: Discussionunclassified
“…Aggregate data from electronic health records (EHRs) were obtained from a subset of healthcare organizations (HCOs) that are associated with the TriNetX research network (TriNetX, Cambridge, MA) as described previously [12][13][14]. TriNetX is a global federated health research network that provides access to real-time EHR data, including demographics, diagnoses, laboratory results, and vital signs.…”
Section: Data Sourcementioning
confidence: 99%